A SYSTEMATIC REVIEW OF MOBILE-ASSISTED VOCABULARY LEARNING AND TEACHING IN ESL/EFL CONTEXT - Muhammad Nawaz; Malini Ganapathy; Sadaf Manzoor; Tess Ezzy; Shahzad Ul Hassan Farooqi (Malaysian Journal of Learning and Instruction)
Purpose - The integration of mobile technology in ESL/EFL contexts has garnered significant attention from contemporary researchers, teachers, and learners due to the advancements in technology, dynamic features, and multimodal applications. With this growing interest, there is a need to synthesize the existing literature and identify current trends in the field.